2012
DOI: 10.5152/akd.2012.123
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of embolic risk factors and adequacy of anti-embolic treatment in patients with atrial fibrillation: a single tertiary center experience

Abstract: ÖZETAmaç: Atriyal fibrilasyon (AF) günümüzde en sık gözlenen kalıcı ritim bozukluğu olmasına rağmen hastalığın prevalansı, risk faktörlerinin sıklığı, uygulanan pıhtı önler tedavinin uygunluğu ve başarısı hakkındaki veriler yetersizdir. Biz bu çalışmada, üçüncül bir merkez olan hastanemizdeki kardiyoloji polikliniğimize başvuran hastalarda AF prevalansını, risk faktörlerinin sıklığını ve uygulanan pıhtı önler tedavinin uygunluğunu güncel kılavuzları göz önünde bulundurarak araştırmayı amaçladık. Yöntemler: Has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
1
8
0
1
Order By: Relevance
“…In our study, we found that the Turkish population patients treated with warfarin had 49.5% TTR levels. Karacağlar et al (17) analyzed the patients with AF in a single-center study, and they found that 167 of 202 patients had regular INR monitoring and the TTR levels were 83.5%. However, they had a very small sample size for reflecting Turkish data.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that the Turkish population patients treated with warfarin had 49.5% TTR levels. Karacağlar et al (17) analyzed the patients with AF in a single-center study, and they found that 167 of 202 patients had regular INR monitoring and the TTR levels were 83.5%. However, they had a very small sample size for reflecting Turkish data.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the TEKHARF (Cardiac Diseases and Risk Factors in Adults in Turkey) study, the prevalence of AF in our country is 1.25% and its overall morbidity is 6.8/100 person-year (3) It is obvious that AF is a significant health problem in our country. While there are many studies assessing the epidemiological data concerning the use of oral anticoagulant medication in patients with AF (4)(5)(6)(7)(8), single center studies on the anticoagulant therapy and the risk of cerebrovascular event have been conducted in our country (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…These patients have high scores; a score evaluation system using a 9 point scale (9-point score evaluation) defi ned as CHA 2 DS 2 -VASc (cardiac failure, hypertension, age ≥ 75 (doubled), diabetes, stroke (doubled), vascular disease, age 65-74 and sex category [female]) acronym [2]. In our country, the studies conducted on AF, stroke and oral anticoagulant usage are mostly unicenter studies with a limited number of patients and CHA 2 DS 2 -VASc score wasn't included [3][4][5]. Since the multicenter studies have been conducted in western and far eastern populations, they do not refl ect the characteristics of the country [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%